ChemInform Abstract: Ligand‐Controlled Divergent C—H Functionalization of Aldehydes with Enynes by Cobalt Catalysts. Issue 25 (June 2016) - Santhoshkumar, Rajagopal; Mannathan, Subramaniyan; Cheng, Chien‐Hong
Abstract: The cobalt‐catalyzed reaction of 1, 6‐enynes (I) with benzaldehyde leads either to aldehydes [cf.